58.8k views
5 votes
How do i get the anser on here please go as in depth as posible

How do i get the anser on here please go as in depth as posible-example-1
User Dlink
by
5.7k points

1 Answer

6 votes

as you should already know to get the inverse of any expression, we start off by doing a quick switcheroo on the variables, and then solve for "y".


\bf \stackrel{f(x)}{y} = \cfrac{x}{x-1}\implies \stackrel{switcheroo}{x=\cfrac{y}{y-1}}\implies x(y-1)=y\implies xy-x=y \\\\\\ -x=y-xy\implies -x=\stackrel{\textit{common factor}}{y(1-x)}\implies \cfrac{-x}{1-x}=y \\\\\\ \cfrac{x}{-(1-x)}=y\implies \cfrac{x}{x-1}=\stackrel{f^(-1)(x)}{y}

User Jey Geethan
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.